Factors affecting safe and healthy diet in older adults in Italy: results of a preliminary study performed in a community-dwelling sample. Issue 3 (23rd August 2019) - Laurenti, P; De Meo, C; Sacchini, D; Spagnolo, AG; Moro, D; Varacca, A; Landi, F; Manes-Gravina, E; Sgadari, A; Bernabei, R; Barbara, A; Ricciardi, W; et al.
Abstract: Objective: To investigate, through a questionnaire, older adults' demographic and socio-economic characteristics, knowledge, attitudes and practices in terms of food safety and healthy diet; and to develop dietary and hygiene indices able to represent participants' nutritional and food safety behaviour, exploring their association with demographic and socio-economic factors. Design: One-year cross-sectional study. Setting: Gemelli Teaching Hospital (Rome, Italy). Participants: People aged ≥65 years, Italian speaking, accessing the Centre of Ageing Medicine. Results: Mean age of the sample was 74 (sd  7·7) years. Subjective perception of a safe diet was high: 64·2 % of respondents believed they have a balanced diet. Interviewees got informed about proper nutrition mainly from television, magazines, newspapers, Internet (29·9 %) and from health professionals (34·8 %) such as dietitians, whereas 15·4 % from general practitioners. Regarding food safety, 33·8 % of participants reported to consume expired food, even more than once per month; between 80 and 90 % of participants reported to follow food safety practices during preparation and cooking, even though 49·3 % defrosted food at room temperature. Calculated dietary and hygiene indices showed that the elderly participants were far from having optimal nutritional and food safety behaviours. Conclusions: These results suggest it is necessary to increase the awareness of older adults in the matter of healthy diet and food safety. Specific and targeted educational interventions for the elderly and their caregivers could improve the adoption of recommended food safety practices and safe nutritional behaviours among older adults.